2011
DOI: 10.1192/bjp.bp.110.085431
|View full text |Cite
|
Sign up to set email alerts
|

Individual music therapy for depression: randomised controlled trial

Abstract: Individual music therapy combined with standard care is effective for depression among working-age people with depression. The results of this study along with the previous research indicate that music therapy with its specific qualities is a valuable enhancement to established treatment practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
211
0
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(273 citation statements)
references
References 21 publications
12
211
0
24
Order By: Relevance
“…Similar results were obtained from a number of arts therapies studies (Erkkilä et al, 2011;Jeong et al, 2005;Thyme et al, 2007). While the current study did not include a control group, it may not be concluded with certainty whether this effect occurred as an implication to the therapy or whether it was due to other reasons, including a possible spontaneous recovery from depression (Ankarberg & Falkenström, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were obtained from a number of arts therapies studies (Erkkilä et al, 2011;Jeong et al, 2005;Thyme et al, 2007). While the current study did not include a control group, it may not be concluded with certainty whether this effect occurred as an implication to the therapy or whether it was due to other reasons, including a possible spontaneous recovery from depression (Ankarberg & Falkenström, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…Regarding the music therapy part, the chosen model was Integrative Improvisational Music Therapy (IIMT), which is a model that was developed at the University of Jyväskylä, Finland, and successfully used for the treatment of depression in a randomised controlled trial (Erkkilä et al, 2011). In IIMT, clients are encouraged to express themselves musically in order to explore their thoughts, memories, emotions, and inner conflicts.…”
Section: Music Therapymentioning
confidence: 99%
“…This finding tallies with the negative emotional bias displayed by depressed patients, who tend to experience more negative emotions than HC. Regarding the recognition of emotions expressed in music, Punkanen et al (Erkkila et al, 2011) found that, compared with HC, depressed patients had significantly higher scores on the recognition of anger and sadness for all musical excerpts. This misinterpretation of emotional valences was also described by Gur andcolleagues in 1992 (Gur et al, 1992), when they showed that depressed patients recognize neutral faces as being rather sad, and happy faces as rather neutral.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies of emotional experience (Dubois et al, 2012;M'bailara et al, 2009), we hypothesized that all the emotional responses of patients in a euthymic state are exaggerated, compared with those of healthy controls (HC), all their emotional responses are exaggerated. Moreover, taking account of previous research on BD using emotional prosody and music (Bozikas et al, 2007;Erkkila et al, 2011), we hypothesized that there is a specific deficit in the experience of negative emotions.…”
Section: Introductionmentioning
confidence: 99%